Search and retrieval of source code using the faceted approach - Mendes, Rodrigo Cavalcante (2008)
Software Reuse has been considered a key concept to increase the quality and productivity of the software development by the reuse of existing artifacts, avoiding build new ones from scratch. However, In order to obtain effective benefits from the software reuse is necessary a set of complementary resources such as: education, active management support and the introduction of appropriate process and tools. In fact, resources that provide mechanism to ease the access of reusable components, such as search and retrieval tools, appear as potential instruments in favor of reuse programs adoption in the organizations. One of the challenges of the search and retrieval tools is how to make that existing components returned have a significant relevance. In this sense, the use of the faceted approach rises as a suitable alternative. This approach proposes the creation of a vocabulary supported by attributes, dividing the components into group of classes based on pre-defined keywords, increasing the level of precision and providing a more flexible classification. Thus, this work presents an extension of search and retrieval tool of reusable components, source code in particular, using the faceted classification approach. In addition, also was developed an auxiliary tool to aid the Domain expert to perform his activities using this approach. Finally, an experimental study evaluates the proposed solution